Association of albumin to globulin ratio with mortality in patients with aneurysmal subarachnoid hemorrhage - Yangchun Xiao; Li Li; Yu Zhang; Shiping Chen; Xin Cheng; Wenqing Wang; Yixin Tian; Jialing He; Lu Jia; Chao You; Fang Fang; Dianxiang Lu (PLoS ONE, 2025)
Background The albumin to globulin ratio (AGR) has been associated with poor outcomes in various diseases, but the association with mortality in aneurysmal subarachnoid hemorrhage (aSAH) is still unclear. Our study aimed to explore the relationship between AGR and short-term case fatality in patients with aSAH. Methods This retrospective study included 3,421 patients with aSAH at West China Hospital, Sichuan University. All Serum AGRs were obtained within 2 days of admission, and patients were categorized into four groups based on their AGR. Cox regression analyses were conducted to assess the relations between AGR and both 30-day and 90-day mortality. Results In 3,421 participants, 339 patients (9.9%) with 30-day mortality, and 407 patients (13.3%) with 90-day mortality. The patients were categorized into four quartiles based on their AGR levels: Q1 (AGR ≤ 1.33), Q2 (AGR: 1.33–1.50), Q3 (AGR: 1.50–1.70), and Q4 (AGR > 1.70). The HR after adjusted for confounders showed significant associations with 30-day mortality, Q2 group (HR 0.72, 95% CI 0.53–0.97), Q3 group (HR 0.72, 95% CI 0.54–0.96), Q4 group (0.53, 95% CI (0.39–0.72)) compared to Q1 group. The association was still significant for 90-day mortality, Q2 group (HR 0.77, 95% CI 0.59–1.01), Q3 group (HR 0.75, 95% CI 0.58–0.98), Q4 group (0.53, 95% CI (0.40–0.71) compared to Q1 group. Conclusions A lower admission AGR was significantly associated with an increased risk for short-term case fatality and poor functional outcomes in patients with aSAH. Further prospective research is essential to confirm our findings and explore the mechanisms behind this association.